Jengkol Peel Extract (Pithecellobium jiringa (Jack) Prain) as a Biofungicide Against Fungus Curvularia sp., the Cause of Leaf Spot Disease on Oil Palm (Elaeis guineensis Jacq) Seedlings - Suyanto, Agus; Agnes Tutik, Purwani Irianti; Akbar, Taufik (Penerbit UiTM, 2022)
Leaf spot disease of oil palm caused by fungus Curvularia sp. is a major disease in Oil Palm Seedlings (Elaeis guineensis Jacq). Implementation of best nursery practices is the key to prevent it. This study aims to determine the antifungal activity of Jengkol peel (Pithecellobium jiringa (Jack) Prain) extract against the fungus Curvularia sp. which is the cause of leaf spot disease in oil palm (Elaeis guineensis Jacq) seedlings. This study was carried out for five months at the Plantation Plant Protection Center (Balai Proteksi Tanaman Perkebunan, BPTP) in Pontianak. Jengkol peel extract was screened for its ability to inhibit Curvularia sp. growth by in vitro technique. The research method used a completely randomized design (CRD) with a single factor, namely the concentration of Jengkol peel extract, P0: as a control (without extract), P1: extract with a concentration of 10%, P2: extract with a concentration of 20%, P3: extract with a concentration of 30%, P4: extract with a concentration of 40%, and P5: extract with a concentration of 50%. Parameters observed were suppression of colony diameter and suppression of colony biomass. The results of the study showed that the administration of Jengkol peel extract in P5 treatment (50% extract concentration) had a major effect on suppressing the diameter of fungal colonies (36.44%) and showed a significant difference between each concentration (p < 0.05), while the P3 treatment (30% extract concentration) was able to suppress colony biomass up to 100%. The use of Jengkol peel (Pithecellobium jiringa (Jack) Prain) extract has potential as bio fungicide based on the effect found on the suppression of growth both from the diameter and biomass of the fungal colony of Curvularia sp.